PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS INKUIRI TERBIMBING (GUIDED INQUIRY) PADA POKOK BAHASAN HIDROLISIS GARAM UNTUK KELAS XI SMA/MA - Ririn Marcella; Maria Erna; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to produce Student Task Sheet (LKPD) based on guided inquiry on salt hydrolysis and to know the response of teachers and students on developed Student Task Sheet. The model used in this research is 4-D through 4 phases : Definition, Design, Development, and Disseminate. The disseminate is not carried out due to takes time. An Analysis of Basic Competence (KD) with indicators that had been integrated with Guided Inquiry stage for being used as reference in developing Student Task Sheet had been produced during the definition stage. The Design stage had produced task sheet that had been designed. The development stage had produced task sheet that had been validated by 3 validators, and it was tested on 2 chemistry teachers and 13 students. Product were validated and were responded based on properness of contens, presentation, language, and design. The result showd that tash sheet had been developed based on four aspects : 95,13% on contents aspect, 95,84% on properness of presentation aspect, 97,92% on properness of language aspect and 93,75% on properness of design aspect. Overall, the average percentage of the task sheet that had been developed was 95,83%. That value included in valid category.Keywords : Student Task Sheet (LKPD), Guided Inuiry, Salt Hydrolisis, 4-D